Food Supply Chain Shocks and the Pivot Toward Local: Lessons From the Global Pandemic - DuPuis, E. Melanie; Ransom, Elizabeth; Worosz, Michelle R. (Frontiers in Sustainable Food Systems, 2022)
Studies of how consumers acquired food provisions during the COVID-19 lockdown indicate that some US consumers and institutional provisioners pivoted to locally produced food. In some locations local food system organizations, along with state governments, created the infrastructure to enable this pivot. Research on this phenomenon – what we call “the local pivot” – has been extensive. However, evidence collected so far has mostly been reports of case studies looking at particular communities. Using Google Trends and Twitter data, we examine whether “the local pivot” was evident as a general trend in the US during the depth of the COVID-19 food supply crisis in 2020, and whether places with high local food infrastructure allowed more people to pivot to local food provisioning. Our Google Trends analysis indicated a temporary rise in searches for local food. However, we found very little discussion of local food systems on Twitter. We then compared three states with a “high,” “medium,” and “low” local food infrastructure based on the Union of Concerned Scientists rankings. We found a weak but positive relationship between places that were classified as high local food system infrastructure and a pivot toward local food reflected on Twitter. We did, however, find strong support for local restaurant businesses during this period on Twitter, although this support did not necessarily reflect a local food system pivot. We acknowledge that Twitter results are not generalizable to the entire population: local food system actors may not be using Twitter in their interactions, so Twitter activity may not reflect local food system activity in general, or COVID food sourcing behavior in particular. However, our results do indicate the need for more research on whether or not the evidence of a pivot to local food systems during COVID in the United States reflected a larger national movement or occurred in just a few scattered communities. Further research on this topic can help ascertain the ability of local food system infrastructure to provide a resilient response to future global food chain crises.